Get more done in less time - Gallagher, Donald; Communication Briefing (Blackwood, N.J. : Communication Briefing, 1991)
This video teach us the latest time management techniques which is more effective.
Presenter: Donald Gallagher
Keywords: Time management; Decision making; Executive -- Time management